Citizenship and Precarious Labour in Canadian Agriculture - Otero, Gerardo; Preibisch, Kerry (Canadian Centre for Policy Alternatives, BC Office, 2015)
Based on interviews with 200 farmworkers, as well as representatives from industry, advocates and civil servants, this study finds that most BC farm workers are subject to hazardous conditions like unsafe transportation, substandard living conditions, long work hours and dangerous equipment. Employment standards for the agricultural sector are only loosely enforced.